2017
DOI: 10.1016/j.pjnns.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Dopa-responsive dystonia or early-onset Parkinson disease – Genotype–phenotype correlation

Abstract: Reported cases confirm that the DRD phenotype may have heterogeneous genetic background and may be caused by point mutations or rearrangements in the GCH1 gene as well as in the PARK2 gene. Differential diagnosis and genetic tests covering the analysis of genes causative for DRD and EO-PD should be obligatory in both disorders diagnostics as DRD, mainly adolescent onset dystonia, may be associated with parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Parkinson disease associated with mutations in parkin [26]. Dystonia is a well-known feature of this genetic subtype of Parkinson disease, although the dystonia is mostly in the limbs [27][28][29]. Docosahexaenoic acid was also potentially abnormal in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson disease associated with mutations in parkin [26]. Dystonia is a well-known feature of this genetic subtype of Parkinson disease, although the dystonia is mostly in the limbs [27][28][29]. Docosahexaenoic acid was also potentially abnormal in CD.…”
Section: Discussionmentioning
confidence: 99%
“…The other reason why we chose risperidone was because it has been shown to be effective at treating psychosis in patients with Parkinson's Disease [ 12 ]. Since recent literature has suggested that dopa-responsive dystonia may be associated with Parkinson's Disease [ 13 , 14 ], we postulated that risperidone would also be effective at treating psychosis in dopa-responsive dystonia.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of monogenic PD forms in Polish populations have analysed the three most common autosomal recessive genes reported in EOPD: PRKN, PINK1, and DJ1 [16,20,23,24,31]. Though typical age at onset for PD is above 60 years, EOPD is defined in different ways.…”
Section: Autosomal Recessive Pd Genesmentioning
confidence: 99%